2016
DOI: 10.1007/s00114-016-1392-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shading on the photosynthetic characteristics and mesophyll cell ultrastructure of summer maize

Abstract: A field experiment was conducted to study the effects of shading on the photosynthetic characteristics and mesophyll cell ultrastructure of two summer maize hybrids Denghai605 (DH605) and Zhengdan958 (ZD958). The ambient sunlight treatment was used as control (CK) and shading treatments (40 % of ambient sunlight) were applied at different growth stages from silking (R1) to physiological maturity (R6) (S1), from the sixth leaf stage (V6) to R1 (S2), and from seeding to R6 (S3), respectively. The net photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…The negative post-silking dry matter accumulation of ZD958, JY877 and SY29 in 2016 was possibly because of leaf and stem rotting caused by intermittent rainfall during grain filling. The reduced post-silking dry matter accumulation may be due to the decreased photosynthetic capacity attributed to light deprivation, which limits the source capacity for grain development [5,6,8,11]. The low SPAD value and photosynthetic rate (unpublished data) under shading indicated that the photosynthetic function deteriorated, and the leaf photoprotection mechanism was probably damaged, thereby decreasing photosynthesis and dry matter accumulation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative post-silking dry matter accumulation of ZD958, JY877 and SY29 in 2016 was possibly because of leaf and stem rotting caused by intermittent rainfall during grain filling. The reduced post-silking dry matter accumulation may be due to the decreased photosynthetic capacity attributed to light deprivation, which limits the source capacity for grain development [5,6,8,11]. The low SPAD value and photosynthetic rate (unpublished data) under shading indicated that the photosynthetic function deteriorated, and the leaf photoprotection mechanism was probably damaged, thereby decreasing photosynthesis and dry matter accumulation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Post-silking shading reduces the number of maize grains because of a limited source capacity [6], and a decreased kernel set is primarily in apical ear regions because of the decreased photosynthesis, the increased abscisic acid level and the nearly halted accumulation of nonstructural carbohydrate [7]. Plants suffering from a low sunlight intensity at the post-silking stage experience a dissolution of their cell membrane, karyotheca, mitochondria and some membrane structures, leading to a decreased photosynthetic capacity [8]. Root physiological properties (dry weight, root/shoot ratio, absorption area) are deteriorated by shading [9].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of climate on cell ultrastructure and the stimulation of several key enzymes that lead to the biogenesis of different substances as a reaction to different environmental factors (biotic and abiotic) is a widespread phenomenon in many plant tissues (see Roshchina and Roshchina 1993;Rios-Estepa et al 2008;Ren et al 2016). Collectively, environmental conditions (especially light and temperature) and the availability of non-mineral nutrients, macronutrients and micronutrients, greatly influence the amount of cells and their biochemical composition (lipids, proteins and carbohydrates) (see Roshchina and Roshchina 1993;Juneja et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, environmental conditions (especially light and temperature) and the availability of non-mineral nutrients, macronutrients and micronutrients, greatly influence the amount of cells and their biochemical composition (lipids, proteins and carbohydrates) (see Roshchina and Roshchina 1993;Juneja et al 2013). In general, all of these factors can affect photosynthesis (Ren et al 2016), thus altering carbon fixation and the allocation of carbon into different types of macromolecules. On the other hand, the cell's macromolecular composition determines its usefulness in cell functioning (Juneja et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the numbers of cloudy/overcast/rainy days from early-June to mid-July in 2016 and 2017 in Yangzhou were 47 and 46, respectively (data available at http://www.tianq ihoub ao.com/lishi/ yangz hou.html). Studies have observed that postsilking shading decreases photosynthetic and electron transport rates Reed, Singletary, Schussler, Williamson, & Christy, 1988;Ren et al, 2016;Zhong, Shi, Li, & Huang, 2014), damages the leaf mesophyll cell ultrastructure (Ren et al, 2016), reduces the activities of enzymes involved in photosynthesis (Sharwood, Sonawane, & Ghannoum, 2014) and the activity of the carbon-concentrating mechanism with increased leakiness (Bellasio & Griffiths, 2014), affects the root morphology and activity indices (Gao, Shi, et al, 2017), increases the grain abscisic acid (ABA) content (Setter, Flannigan, & Melkonian, 2001), and reduces the endosperm cell number and volume (Jia, Li, Dong, & Zhang, 2011). These adverse effects reduce the dry matter and nutrient accumulation (Cui et al, 2013;Liu & Tollenaar, 2009;Mbewe & Hunter, 1986), increase aborted grain numbers due to the nearly halted filling of apical grains, and decrease grain weight (Cui, Camberato, Jin, & Zhang, 2015;Reed et al, 1988;Setter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%